(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: Head traumas are prevalent in children with mild severity and without commitment of delayed brain injuries. The aim of present study was to detect the mild head trauma (MHT) children with high risk of brain injuries for avoidance of unnecessary interventions. Methods: This cross-sectional study considered 100 children under 2 years old with MHT in Kashani and Alzahra Hospitals between March 2011 and August 2011, Isfahan, Iran. Data was gathered by these project executives including the radiologist reports and the patients past medical history. The patients were divided into normal and abnormal CT scan and reduction of consciousness level, vomiting and the other variables were considered. Results: The results were obtained from evaluation of 100 files from the patients with mean age 18±7.1 month. CT scan findings showed that 55 percent of the patients were abnormal and had burn injuries including skull fracture, epidural hemorrhage, skull contusion, and arachnoids hemorrhage. The incidence of repeated vomiting and reduction of consciousness level in patients with non-normal CT scan was more than normal group while this difference was not significantly different. Also according to CT scan findings there was no statistically significant difference between patients with repeated vomiting or reduced consciousness level (P>0.05). Conclusions: This study results showed that there is not significantly difference between vomiting incidence, deceased level of consciousness and CT scan results. These criteria were not considered separately as only factors for burn trauma of performing CT scan in MHT patients. DOI: http://dx.doi.org/10.3329/bjms.v13i2.15053 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.140-144